Overview of Tanjung Semeti Training Area on The VFR Corridor Path - John Richard Madson; Nunuk Praptiningsih (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Zainuddin Abdul Madjid International Airport serves daily training flights and has a training area determined in the "Tanjung Semeti Area" where the location is also the same with the “Tanjung Semeti” checkpoint on the VFR Corridor. The purpose of this research is to review Tanjung Semeti training area to the VFR corridor path and seek solutions from potential safety risks (hazard) in that area. The research method used is a qualitative approach with data collection techniques through observation. The results of the study revealed that the same location causes VFR flight that passes through VFR corridor overlap with the training flight in the training area causing a potential safety risk for both flights. In an effort to be free from potential flight safety risks, by creating a training area at Tanjung Penggeroh or by optimizing the airspace of Sumbawa as a location for a training area will ensure the safety, efficiency and regularity of air traffic in the airspace of Zainuddin Abdul Madjid International Airport.